Análisis e implementación del Marketing Digital en la fidelización de clientes mediante el Community Manager en empresas del sector fitness en Lima Metropolitana - Villanueva Herrera, José Rolando (2023)
The purpose of this research is to demonstrate the importance of Digital Marketing, applied through the Community Manager, with the aim of achieving customer loyalty in companies in the fitness sector; through its social networks, such as Instagram and Facebook, which are the social networks where the brand currently has a presence in the market. This company is venturing into the sports field, with the sale of accessories and natural supplements. Likewise, this research makes use of 62 surveys, applied to regular customers of the same company in the city of Lima, who were contacted via email and WhatsApp. Resulting in the evident existence of the relationship between Digital Marketing and the Community Manager, as reliable means in achieving the objectives set. It is worth noting the importance of both factors working together, thus achieving more satisfied customers, showing a distinctive to the competition and thus making them more loyal to the brand.